Design thinking framework of experience innovation - Grigoryeva, Svetlana (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Innovation remains one of the key drivers of sustainable and successful business. The variety of innovation approaches such as open models, intersectional thinking and co-creation tackles the challenge of viable novel offerings across the world. These approaches have certain similarities and their elements constitute design thinking. Recent market and society trends such as technological advances and globalization have intensify companies’ interaction with customers. Emotional engagement, pleasing communication and delight have gained equal to functionality importance. The complex of these components constitutes consumer experience. Academic research conceptualizes these changes by introducing customer-centered innovation, which replaces product-oriented approaches. However, both methods omit experience concept and provide fragmented explanation of experience innovation. Experience is an essential process of offering perception, which drives customer decisions. Therefore, an agenda of experience innovation development can systemize and explain the mechanisms of experience innovation. The purpose of this study is to create and explain the stage process framework of experience innovation by the means of design thinking approach. The research proceeds in accordance with the following sub-objectives: 1. Conceptualization of consumer experience through customer value. 2. Creation of experience innovation framework by the means of design thinking. This study is conducted by the means of conceptual research methods. The main theoretical contribution of the study is creation of the integrated framework of consumer experience innovation. The elaboration of design thinking agenda and methods applied to experience design builds the guidelines of experience innovation development. This research synthesizes the conceptual elements of the framework that resolves inconsistencies and duplications of theories. This essential clarification simplifies application of the experience innovation agenda, which can be useful for the wide range of specialists, from marketing to strategists, and from managers to entrepreneurs, willing to offer compelling experience to customers. The study highlights the crucial role of consumer experience in maintaining customer loyalty and designs the roadmap of innovating experience through the communication with customers.